Open:Mucosal‐luminal interface proteomics reveals biomarkers of pediatric inflammatory bowel disease‐associated colitis. (May 2018) - Deeke, Shelley A.; Starr, Amanda E.; Ning, Zhibin; Ahmadi, Sara; Zhang, Xu; Mayne, Janice; Chiang, Cheng‐Kang; Singleton, Ruth; Benchimol, Eric I.; Mack, David R.; Stintzi, Alain; Figeys, Daniel
Abstract : OBJECTIVE: Improved biomarkers are an unmet clinical need for suspected inflammatory bowel disease (IBD). Need is greatest for children, since current biomarkers suffers from low specificity, particularly in this population; thus, invasive testing methods, with the accompanying risk of complications, are necessary. Additionally, current biomarkers do not delineate disease extent assessment for ulcerative colitis (UC), a factor involved in therapeutic decisions. METHODS: Intestinal mucosal‐luminal interface (MLI) aspirates from the ascending colon (AC) and descending colon (DC) were collected during diagnostic colonoscopy from treatment‐naïve children. The MLI proteomes of 18 non‐IBD and 42 IBD patients were analyzed by liquid chromatography mass spectrometry. Analyses of proteomic data generated protein panels distinguishing IBD from non‐IBD and pancolitis from non‐pancolitis (UC disease extent). Select protein biomarkers were evaluated in stool samples by enzyme‐linked immunosorbent assay ( n = 24). RESULTS: A panel of four proteins discriminated active IBD from non‐IBD (discovery cohort) with a sensitivity of 0.954 (95% confidence interval (CI): 0.772–0.999) and >0.999 (95% CI: 0.824–1.00) for the AC and DC, respectively, and a specificity of >0.999 (AC, 95% CI: 0.815–1.00; DC, 95% CI:0.692–1.00) for both the AC and DC. A separate panel of four proteins distinguished pancolitis from non‐pancolitis in UC patients with sensitivity >0.999 (95% CI: 0.590–1.00) and specificity >0.999 (95% CI: 0.715–1.00). Catalase ( p < 0.0001) and LTA4H ( p = 0.0002) were elevated in IBD stool samples compared to non‐IBD stool samples. CONCLUSION: This study identified panels of proteins that have significantly different expression levels and contribute to accurate IBD diagnosis and disease extent characterization in children with UC. Biomarkers identified from the MLI demonstrate transferable results in stool samples.